2020
DOI: 10.1038/s41598-020-70694-8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of cytotoxic T lymphocyte-mediated anticancer response against tumor interstitium-simulating physical barriers

Abstract: Tumor antigen-specific cytotoxic T lymphocyte (CTL) is a promising agent for cancer therapy. Most solid tumors are characterized by increased interstitial fluid pressure (IFP) and dense collagen capsule, which form physical barriers to impede cancer treatment. However, it remains unclear how CTL-mediated anticancer response is affected at the presence of these obstacles. Using a microfluidic-based platform mimicking these obstacles, we investigated the migration characteristics and performance of anticancer re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 56 publications
0
17
0
Order By: Relevance
“…Cytotoxic T lymphocytes (CTLs) play a vital role in immunotherapy by recognizing specific antigens on tumor cells 121 . Moreover, CTLs can impose perforin on target cells and deliver granzymes, which leads to pore formation and cytolysis 122 ; this morphology shares similarities with pyroptotic cell death.…”
Section: Correlation Between Pyroptosis and Modulation Of Cancer Immunitymentioning
confidence: 99%
“…Cytotoxic T lymphocytes (CTLs) play a vital role in immunotherapy by recognizing specific antigens on tumor cells 121 . Moreover, CTLs can impose perforin on target cells and deliver granzymes, which leads to pore formation and cytolysis 122 ; this morphology shares similarities with pyroptotic cell death.…”
Section: Correlation Between Pyroptosis and Modulation Of Cancer Immunitymentioning
confidence: 99%
“…[34] On the contrary, migration and infiltration of T cells is significantly reduced, once a certain collagen density is reached, [34] in example, when space between the fibrils is smaller than 5 µm. [32] A recent study by Sun et al showed that discoidin domain receptor 1 (DDR1)'s extracellular domain (DDR1-ECD) facilitates collagen fiber alignment, hence immune exclusion. Upon knock-out and capture by monoclonal antibodies specific to DDR1-ECD, T cell invasion was restored, resulting in triple-negative breast cancer remission for 10 out of 18 mice.…”
Section: Ecm Microarchitecture and Stiffness Influence Tumor Infiltra...mentioning
confidence: 99%
“…There were also studies using some physical methods (e.g., hyperthermia, [83] and photodynamic therapy [84] ) for the same purpose. Furthermore, Chen et al [32] showed that antigen-specific transmigration of T cells into a microfluidics-based cancer model was stalled under elevated hydrostatic pressure (see Figure 1A). In summary, extravasation only is possible from peripheral well-organized vessels which are exposed to low IFP.…”
Section: High Ifp and If Suppress T Cell Infiltrationmentioning
confidence: 99%
“…[34] On the contrary, migration and infiltration of T cells is significantly reduced, once a certain collagen density is reached, [34] in example, when space between the fibrils is smaller than 5 µm. [32] A recent study by Sun et al showed that discoidin domain receptor 1 (DDR1)'s extracellular domain (DD1-ECD) facilitates collagen fiber alignment, hence immune exclusion. Upon knock-out and capture by monoclonal antibodies specific to DDR1-ECD, T cell invasion was restored, resulting in triple-negative breast cancer remission for 10 out of 18 mice.…”
Section: Ecm Microarchitecture and Stiffness Influence Tumor Infiltrationmentioning
confidence: 99%
“…[76] In a different study, IFP was significantly decreased with the anti-PDGF receptor kinase antibody (imatinib) with similar positive results on patient's survival. [67] Furthermore, Chen et al [32] showed that antigen-specific transmigration of T cells into a microfluidics-based cancer model was stalled under elevated hydrostatic pressure (see Figure 1A). In summary, extravasation only is possible from peripheral well-organized vessels which are exposed to low IFP.…”
Section: High Ifp and If Suppress T Cell Infiltrationmentioning
confidence: 99%